The design and proof of concept for a CD8+ T cell‐based vaccine inducing cross‐subtype protection against influenza A virus. Issue 1 (13th November 2012) - Tan, Amabel C L; Deliyannis, Georgia; Bharadwaj, Mandvi; Brown, Lorena E; Zeng, Weiguang; Jackson, David C
Abstract : In this study, we examined the reactivity of human peripheral blood mononuclear cells to a panel of influenza A virus (IAV) CD8 + T‐cell epitopes that are recognised by the major human leukocyte antigen (HLA) groups represented in the human population. We examined the level of recognition in a sample of the human population and the potential coverage that could be achieved if these were incorporated into a T‐cell epitope‐based vaccine. We then designed a candidate influenza vaccine that incorporated three of the examined HLA‐A2‐restricted influenza epitopes into Pam2Cys‐based lipopeptides. These lipopeptides do not require the addition of an adjuvant and can be delivered directly to the respiratory mucosa enabling the generation of local memory cell populations that are crucial for clearance of influenza. Intranasal administration of a mixture of three lipopeptides to HLA‐A2 transgenic HHD mice elicited multiple CD8 + T‐cell specificities in the spleen and lung that closely mimicked the response generated following natural infection with influenza. These CD8 + T cells were associated with viral reduction following H3N1 influenza virus challenge for as long as 3 months after lipopeptide administration. In addition, lipopeptides containing IAV‐targeting epitopes conferred substantial benefit against death following infection with a virulent H1N1 strain. Because CD8 + T cell epitopes are often derived from highly conserved regions of influenza viruses, such vaccines need not be reformulated annually and unlike current antibody‐inducing vaccines could provide cross‐protective immunity against newly emerging pandemic viruses.